Semi Wireless Underwater Rescue Drone with Robotic Arm - Ishrat Jacy Meem; Safwat Osman; Khadem Md Habibul Bashar; Nazrul Islam Tushar; Riasat Khan (Journal of Robotics and Control (JRC), 2022)
Wireless communication with underwater drones plays a vital role in rescuing an after-ship accident, and it is considered one of the most challenging technologies nowadays. The wireless underwater drone also contributes significantly to navy, gas and oil companies, underwater infrastructure, aquaculture industry, commercial diving, and deep archeological investigations. Bangladesh, a developing country with many rivers and seashores used by many water transport vehicles, faces boat and ship accidents as a typical scenario every year. Many lives, dead bodies, ships, boats, and valuable objects do not get rescued because of the lifetime risk of the divers or the rescue team. The rescue operation is exceptionally troublesome because of the absence of wireless underwater drone technology at the cheapest cost, whose innovation and function are very challenging for Bangladesh. Considering these problematic situations, in this paper, we have proposed a prototype of a semi wireless underwater drone designed and structured with the best quality PVC pipe of 6mm diameter, considering the weight as lowest as possible, maintaining its buoyancy properly. In this prototype, we have used three propellers, each connected with three servo motors, to move it up, down, back, and forth. A robotic arm is also utilized to rescue objects from under the water, and a 4K HD EKEN camera and two waterproof fog lights to search and visualize underwater objects on the mobile screen from the land. For wireless communication between the controller and the drone, we have used two nRF24L01 modules; one is for the controller, and the other is for the drone’s receiver to send and obtain the signals from the controller to the drone. 12V and 24V lithium-ion batteries are employed as power sources for the controller and receiver, respectively. Finally, real experimental tests of the proposed underwater device were performed in a swimming pool facility.